Advances in Cement Composite Materials (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The aim of the Special Issue entitled "Advances in Cement Composite Materials" was to present current trends and advances in cement composite materials not only based on ordinary Portland cement (OPC) and natural aggregates but also in the use of other materials or raw materials incorporated into the cement matrix.